The Agricultural Model Intercomparison and Improvement Project (AgMIP): Integrated regional assessment projects - Rosenzweig, Cynthia; Jones, James W.; Hatfield, Jerry L.; Mutter, CZ; Adiku, Samuel G.K.; Ahmad, A.; Beletse, Y; Gangwar, B; Dileepkumar, Guntuku; Kihara, Job Maguta; Masikati, Patricia; Paramasivan P; et al. (World Scientific Publishing, 2012)
The following sections are included: Introduction. AgMIP Structure and Scientific Approach. AgMIP Regional Activities. AgMIP Sub-Saharan Africa Regional Projects. Climate change impacts on West African Agriculture (CIWARA) — A regional assessment. Impacts of climate variability and change on agricultural systems in Eastern Africa while enhancing the region's capacity to undertake integrated assessment of vulnerabilities to future changes in climate. Southern Africa Agricultural Model Intercomparison and Improvement Project (SAAMIIP). Crop-livestock intensification in the face of climate change: Exploring opportunities to reduce risk and increase resilience in Southern Africa using an integrated multi-modeling approach. Knowledge enhancement for modeling in climate change: Capacity-building in Southern, Western, and Eastern Africa. AgMIP South Asia Regional Projects. Assessing climatic vulnerability and projecting crop productivity using integrated crop and economic modeling techniques. Strengthening simulation approaches for understanding, projecting, and managing climate risks in stress-prone environments across the central and Eastern Indo-Gangetic Basin. Integrated assessment of climate change impacts on principal crops and farm household incomes in Southern India. Modeling the impacts of a variable and changing climate on rice and sugarcane agricultural systems in Sri Lanka. Enhancing capacities of the AgMIP South Asia regional teams through capacity-building workshops and knowledge-sharing platforms. Conclusions. Acknowledgments. Reference.